Intrinsic Motivation and Employee Performance Improvement in Educational Organizations - Erna Ngala; Beatrix Lapalelo; Imran, Treesje (Research Horizon, 2025)
The main issue addressed in this study is the lack of organizational attention to the development of employees' intrinsic motivation, particularly within religious educational institutions, which has led to decreased productivity, loyalty, and job satisfaction. This study aims to gain an in-depth understanding of the role of intrinsic motivation in enhancing employee performance, and  to identify managerial and organizational cultural factors that either support or hinder the realization of such motivation. The research employs a qualitative approach through a case study at Sekolah Tinggi Teologi Yerusalem Baru  Manado, utilizing data collection techniques including in-depth interviews, participant observation, and document analysis. Data were analyzed thematically using the framework of Braun and Clarke. The findings indicate that intrinsic motivation significantly influences performance, as employees who experience autonomy, competence, and social relatedness demonstrate higher levels of loyalty and productivity. Supporting factors identified include participatory leadership, a spiritual organizational culture, and flexible working arrangements. Conversely, the obstacles observed comprise limited training opportunities, the absence of regular evaluations, and financial constraints. The implications of these findings suggest that organizations, particularly in the education sector, need to design managerial strategies focused on strengthening intrinsic motivation through value-based policies, non-material rewards, and the development of a work environment that fosters employees' psychological growth.